Flood did not cause the taxonomic and functional homogenization of Chironomidae (Diptera) community in a Neotropical floodplain - Silva, João Pabllo Silva da; Petsch, Danielle Katharine [UNESP] (FapUNIFESP (SciELO), 2024)
Aim: We investigated the hypothesis that flood decreases the taxonomic and functional beta diversity of Chironomidae (Diptera) larvae among floodplain lakes, causing biotic homogenization. Methods: We collected benthic samples using a modified Petersen grab in 18 lakes in a flood period (March 2011) and a drought period (September 2011) in the Upper Paraná River floodplain. We compared the taxonomic and functional beta diversity of Chironomidae among lakes in flood and drought periods using a multivariate dispersion analysis (PERMDISP). Results: We found similar taxonomic and functional beta diversity of the Chironomidae between hydrological periods. Conclusions: We did not find evidence of biotic homogenization due to flood pulse. Our findings suggest other mechanisms besides increasing connectivity and environmental similarity due to flood pulse that may structure the benthic community, such as variation in the identity of flood-tolerant morphospecies across lakes.
A cheia não causou homogeneização taxonômica e funcional da comunidade de Chironomidae (Diptera) em uma planície de inundação neotropical
Keywords: beta diversity; biotic homogenization; Upper Paraná River floodplain; zoobenthos